Functional progression in post-osteoporotic fracture: A case study - Sérgio Caseiro; Paula Rocha; Isabel Neves; Carlos Pontinha; Ana Rita Batista; Gina Monteiro; Luís Matos; Filipe Cunha Santos; Ana Sofia Pinto; Sara Paiva Dinis; Joana Ferreira; Cláudia Vaz (Open Journal of Orthopedics and Rheumatology - Peertechz Publications, 2021)
Introduction: Osteoporosis is characterized by a loss of bone mass along with alterations in its structure, with subsequent increase in bone fragility and susceptibility to fractures, ultimately reinforcing the importance of its prevention by the reduction of the risk of falling. In this paper we propose to analyze the functional progression of a patient, integrated in a multidisciplinary program (TOMBO-Therapeutic Occupational Multidisciplinary approach to the Benefit of Osteoporosis), after an osteoporotic fracture. Methods: Retrospective descriptive case-study of the first patient included in the TOMBO program. Data were gathered for Time Up and Go Test (TUGT), Sit to Stand in 30 secs. (SS-30), 10m Walking Test (10m-WT), Barthel Index (BI) and Morse Scale (MS) in 3 different moments: baseline (ward, at discharge: M0), 2 and 6-months after surgery (multidisciplinary appointments: MD2, MD6). Results: TUGT- M0: no capability; MD2: 18,8 secs.; MD6: 8 seg. SS-30 - M0: no capability; MD2: 9 stands; MD6: 10 stands. 10m-WT - M0: 30 secs.; MD2: 13 secs.; MD6: 8 secs. BI - M0: 60; MD2, 80; MD6: 100. MS - M0: 85, MD2: 50; MD6: 15. Conclusion: This case-study revealed us that the first patient admitted to this innovative multidisciplinary approach improved some functional parameters (level of dependency and risk of falling) as shown by its favorable progression on the tests and scales applied.